The dynamic effects of income tax changes in a world of ideas - James Cloyne; Joseba Martinez; Haroon Mumtaz; Paolo Surico (Queen Mary University of London, School of Economics and Finance, 2023)
Using a narrative identification of US tax changes over the post-WWII period, we show that corporate income tax cuts foster R&D spending and innovation, leading to a persistent increase in aggregate productivity and output. In contrast, changes in the average personal income tax rate have mostly short-term effects. An estimated endogenous productivity model highlights the role of "applied research" -over and above formal R&D- as a main force behind these results, and suggests a social rate of return to investment in innovation between 20% and 75%.
Keywords: 23; E62; O32; O34; O38; 330; corporate taxes; narrative identification; TFP; R&D; technological adoption